Subclinical myocardial injury, coagulopathy, and inflammation in COVID-19: A meta-analysis of 41, 013 hospitalized patients. (June 2022) - Ogungbe, Oluwabunmi; Kumbe, Baridosia; Fadodun, Oluwadamilola Agnes; Latha, T.; Meyer, Diane; Asala, Adetoun Faith; Davidson, Patricia M.; Dennison Himmelfarb, Cheryl R.; Post, Wendy S.; Commodore-Mensah, Yvonne
Highlights: In hospitalized COVID-19 patients, there was a high prevalence of underlying comorbidities. Elevated biomarkers of subclinical myocardial injury were significantly associated with severe COVID-19 and death. Recovered COVID-19 patients may benefit from minimally invasive assessment for myocardial injury markers. There is evidence of persisting symptoms suggestive of complications in patients recovered from COVID-19. Abstract: Background: Infection with the SARS-CoV-2 virus can lead to myocardial injury, evidenced by increases in specific biomarkers and imaging. Objective: To quantify the association between biomarkers of myocardial injury, coagulation, and severe COVID-19 and death in hospitalized patients. Methods: Studies were identified through a systematic search of indexed articles in PubMed, Embase, CINAHL, Cochrane, Web of Science, and Scopus, published between December 2019 to August 2021. Effect estimates from individual studies for association between markers of myocardial injury (Troponin), myocardial stretch (N-terminal-pro hormone BNP, NT-proBNP), and coagulopathy (D-Dimer) and death or severe/critical COVID-19 were pooled using inverse variance weighted random-effects model. Odds Ratios (OR), Hazard Ratios (HR), and 95% Confidence Intervals (CI) were pooled separately and reported by outcomes of critical/severe COVID-19 and death. A meta -analysis of proportions was also performed to summarize the pooled prevalence of co-morbidities in patients hospitalized with COVID-19. Results: We included 62 articles, with a total of 41, 013 patients. The pooled proportion of patients with history of hypertension was 39% (95% CI: 34–44%); diabetes, 21% (95% CI: 18%–24%); coronary artery disease, 13% (95% CI: 10–16%); chronic obstructive pulmonary disease, 7% (95% CI: 5–8%); and history of cancer, 5% (95% CI: 4–7%). Elevated troponin was associated with higher pooled odds of critical/severe COVID-19 and death [Odds Ratio (OR: 1.76, 95% CI: 1.42–2.16)]; and also separately for death (OR: 1.72, 95% CI: 1.32–2.25), and critical/severe COVID-1919 (OR: 1.93, 95% CI: 1.45–2.40). Elevations in NT-proBNP were also associated with higher severe COVID-19 and death (OR: 3.00, 95% CI: 1.58–5.70). Increases in D-dimer levels was also significantly associated with critical/severe COVID-19 and death (pooled OR: 1.38, 95% CI: 1.07–1.79). Conclusions: This meta-analysis synthesizes existing evidence showing that myocardial injury, and coagulopathy are complications of COVID-19. The durability of these complications and their contributions to long-term cardiac implications of the disease is still being investigated. Patients who have recovered from COVID-19 may benefit from minimally invasive assessment for markers of myocardial injury, stretch and coagulopathy for early risk stratification purposes.